2019
DOI: 10.1109/tifs.2018.2841870
|View full text |Cite
|
Sign up to set email alerts
|

Boundaries as an Enhancement Technique for Physical Layer Security

Abstract: In this paper, we study the receiver performance with physical layer security in a Poisson field of interferers. We compare the performance in two deployment scenarios: (i) the receiver is located at the corner of a quadrant, (ii) the receiver is located in the infinite plane. When the channel state information (CSI) of the eavesdropper is not available at the transmitter, we calculate the probability of secure connectivity using the Wyner coding scheme, and we show that hiding the receiver at the corner is be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It was observed that the first‐hop feedback delay guards against secrecy throughput loss, unlike the second hop. In contrast, while focusing on receiver performance with PLS in a Poisson field of interferers, 13 results show that the receiver hidden at the given angle at high rates poses great benefits to the transmitted codewords. However, at low transmission rates, the reverse is the case.…”
Section: Related Workmentioning
confidence: 92%
See 3 more Smart Citations
“…It was observed that the first‐hop feedback delay guards against secrecy throughput loss, unlike the second hop. In contrast, while focusing on receiver performance with PLS in a Poisson field of interferers, 13 results show that the receiver hidden at the given angle at high rates poses great benefits to the transmitted codewords. However, at low transmission rates, the reverse is the case.…”
Section: Related Workmentioning
confidence: 92%
“…Channel capacity and computational complexity have remained very common as the adopted metrics 19 . Relatively diverse techniques implemented so far include signal processing techniques, 16 diversity techniques, 18 cooperative jamming, 20,21,23,29 AN and BF, 17,31,32 and boundary techniques 13 . These enhancement techniques, among others, are summarized in Figure 2.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The connection probability is often associated with wireless network reliability, e.g., to prevent disruption due to short radio range, wireless node sparsity, energy resources, cyber attacks, random failures, background noise, etc. The analytical results described above are needed if one is interested for example in analysing the reliability assurance of wireless networks [Lar14] or when developing wireless security and trust protocols that are tailored to specific network deployments [Coo14a,Kou19], or when considering routing protocols in wireless sensor networks [Fu17]. Also,global and local connectivity metrics can be used to enhance wireless localization when positioning devices like GPS are unavailable [Ngu15].…”
Section: Applications Of Connectivitymentioning
confidence: 99%